2015
DOI: 10.1038/nature13978
|View full text |Cite
|
Sign up to set email alerts
|

The paraventricular thalamus controls a central amygdala fear circuit

Abstract: Appropriate responses to an imminent threat brace us for adversities. The ability to sense and predict threatening or stressful events is essential for such adaptive behavior. In the mammalian brain, one putative stress sensor is the paraventricular nucleus of the thalamus (PVT), an area that is readily activated by both physical and psychological stressors1-3. However, the role of PVT in the establishment of adaptive behavioral responses remains unclear. Here we show in mice that PVT regulates fear processing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
436
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 447 publications
(462 citation statements)
references
References 28 publications
25
436
1
Order By: Relevance
“…The posterior PVT has robust projections to the CeA, BLA, and bed nucleus of the stria terminalis (Li and Kirouac 2008;Hsu et al 2014), making it well-placed to influence fear expression. The most prominent projection originating from the posterior PVT is to the lateral division of the CeA (CeL) (Li and Kirouac 2008;Vertes and Hoover 2008) and selective suppression of CeL-projecting PVT neurons impaired fear retrieval (Do-Monte et al 2015;Penzo et al 2015) and retrieval remained impaired the day after the silencing of these neurons (Do-Monte et al 2015). The PVT is necessary for CS-elicited fear when animals are tested in either the same (Padilla-Coreano et al 2012;Li et al 2014;Do-Monte et al 2015) or a different (Penzo et al 2015) context as conditioning, and PVT neurons are activated when rats are returned to a context previously associated with footshock (Beck and Fibiger 1995;Yasoshima et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The posterior PVT has robust projections to the CeA, BLA, and bed nucleus of the stria terminalis (Li and Kirouac 2008;Hsu et al 2014), making it well-placed to influence fear expression. The most prominent projection originating from the posterior PVT is to the lateral division of the CeA (CeL) (Li and Kirouac 2008;Vertes and Hoover 2008) and selective suppression of CeL-projecting PVT neurons impaired fear retrieval (Do-Monte et al 2015;Penzo et al 2015) and retrieval remained impaired the day after the silencing of these neurons (Do-Monte et al 2015). The PVT is necessary for CS-elicited fear when animals are tested in either the same (Padilla-Coreano et al 2012;Li et al 2014;Do-Monte et al 2015) or a different (Penzo et al 2015) context as conditioning, and PVT neurons are activated when rats are returned to a context previously associated with footshock (Beck and Fibiger 1995;Yasoshima et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…CeL is the output nucleus of the amygdala (FIGURE 1A) (98,484,543,544), but it also participates in its acquisition and consolidation (345). CeM is a major regulator of fear learning via the gating of CeL cells (124,345,496). The LA and to a large extent its larger neighbor, the BLA nuclear complex, are rather input nuclei, as will be seen (98, 324,329,335,336,350,380,448,465,561).…”
Section: Hippocampus Amygdala Infralimbic Ventromedial Prefrontmentioning
confidence: 96%
“…Solid recent evidence using in part optogenetic methods has shown that the PVT innervates and regulates CeL neuronal activity, both during (496) and 7 and 24 days after cellular consolidation of fear conditioning (429), and during fear retrieval (429,496). The PVT input acts upon somatostatin-containing neurons of CeL, but not in neurons that do not contain this peptide (429).…”
Section: Hippocampus Amygdala Infralimbic Ventromedial Prefrontmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible that a functional interaction between ACC and PL neurons, associated with preparatory attention in rats, could be disrupted in the present study . Our Cre-dependent viral approach in mouse provides a template for future circuit-specific chemogenetic studies for alternative combinatorial approaches to address such possibilities; replacing AAV8-Cre with retrograde traveling Canine adenovirus type 2 (CAV)-Cre in axonal projecting areas will permit Cre expression only within unique projection circuits (Boender et al, 2014;Carter et al, 2013;Penzo et al, 2015). This chemogenetic dissection approach can serve as a powerful tool to deduce which circuits inhibited by global dACC inactivation primarily contribute to attention deficits.…”
Section: Inactivation Of Dacc Neurons Disrupts Attention In Mousementioning
confidence: 99%